Ceftazidime-assisted synthesis of ultrasmall chitosan nanoparticles for biofilm penetration and eradication of Pseudomonas aeruginosa - Xiaoran Zheng; Min Gao; Liangquan Wu; Xin Lu; Qiuqi Lin; Hai Zhong; Yingfei Lu; Yunlei Zhang; Xiuwei Zhang (Scientific Reports, 2023)
Abstract Pseudomonas aeruginosa (P. aeruginosa) infections present a grave threat to immunocompromised individuals, particularly those with cystic fibrosis due to the development of bacterial biofilms. In this study, we engineered self-assembling chitosan-ceftazidime nanoparticles (CSCE) capable of effectively penetrating biofilms and eradicating P. aeruginosa. The CSCE nanoparticles were synthesized through ionic cross-linking, combining negatively charged ceftazidime with positively charged chitosan, resulting in uniform nanoparticles measuring approximately 40 nm in diameter, exhibiting high dispersity and excellent biocompatibility. Remarkably, these nanoparticles exhibited significant inhibition of P. aeruginosa growth, reduced pyocyanin production, and diminished biofilm formation, achieving a maximum inhibition rate of 22.44%. Furthermore, in vivo investigations demonstrated enhanced survival in mice with abdominal P. aeruginosa infection following treatment with CSCE nanoparticles, accompanied by reduced levels of inflammatory cytokines Interleukin-6 (125.79 ± 18.63 pg/mL), Interleukin-17 (125.67 ± 5.94 pg/mL), and Tumor Necrosis Factor-α (135.4 ± 11.77 pg/mL). Critically, mice treated with CSCE nanoparticles showed no presence of bacteria in the bloodstream following intraperitoneal P. aeruginosa infection. Collectively, our findings highlight the potential of these synthesized nanoparticles as effective agents against P. aeruginosa infections.